Genome-Wide Analysis of DoSPX Genes and the Function of DoSPX4 in Low Phosphorus Response in Dendrobium officinale - Liu, Lin; Xiang, Haoxin; Song, Jingjing; Shen, Huimin; Sun, Xu; Tian, Lingfeng; Fan, Honghong (Frontiers in Plant Science, 2022)
Dendrobium officinale Kimura et Migo is a famous Chinese herb. D. officinale grows on rocks where the available phosphorus is low. The SPX family plays a critical role in maintaining Pi homeostasis in plants. In this paper, 9 SPX family genes were identified in the genome of D. officinale. Bioinformatics and qRT-PCR analysis showed that DoSPXs were involved in response to −Pi stress and had different expression patterns. DoSPX4, which had a unique expression pattern, was clustered with AtSPX4 and OsSPX4. Under −Pi treatment, the expression level of DoSPX4 reached a peak on 5 d in roots, while showing a downward trend in the aboveground parts. DoSPX4 was located on the cell membrane. Overexpression DoSPX4 promoted Pi content in the stem and the expression level of NtPHT1/2 in Nicotiana tabacum. The results of Yeast two-hybrid showed that DoSPX4 could interact with Phosphate High-Affinity Response factor (DoPHR2). These results highlight the role of DoSPX4 in response to low phosphorus, which provides a theoretical basis for further study on the response mechanism of −Pi in D. officinale.